Omega 3 or Creatine Supplementation in Older Adults and its Impact on Cognitive Function: A Systematic Review - López-Sebastiani, Valeria A. (2024)
The systematic review was carried out using the PRISMA methodology and focused on the search for scientific articles in which the effects of omega-3 or creatine supplementation in adults over 60 years of age and its effect on cognitive function had been investigated. The search criteria were supplementation, omega 3, creatine, older adults, memory, function and cognitive impairment. The exclusion criteria were athletes and people under 60 years of age. Articles from PubMed, ScienceDirect and SciELO were included. 223 articles were found investigating the effect of omega-3 supplementation and 25 articles on creatine supplementation, of which 29 and 3 were selected that met the inclusion and exclusion criteria respectively for each group. Concluding that adequate consumption of sources of omega 3 and creatine has a preventive benefit against memory conditions and cognitive deterioration related to aging, since it intervenes in the structure and function of the brain. These findings highlight the importance of a balanced diet and the possible usefulness of supplements in maintaining cognitive health in the older adult population.